The role of 5G in enhancing IOT connectivity: a systematic review on applications, challenges, and future prospects - Shankha Goswami; Surajit Mondal (Big Data and Computing Visions)
The rapid evolution of the Internet of Things (IoT) has transformed various industries by enabling the seamless interconnection of devices and systems, thus driving significant improvements in efficiency, productivity, and innovation. Through IoT, sectors such as healthcare, manufacturing, transportation, and smart cities have been able to deploy interconnected devices that monitor, analyze, and automate tasks, creating a more responsive and data-driven operational environment. However, existing wireless communication networks, particularly 4G LTE, have presented limitations in terms of speed, latency, and connectivity that have hindered the full potential of IoT applications. For instance, IoT-driven systems in autonomous vehicles or remote medical devices require extremely low latency and reliable data transmission, demands that 4G networks struggle to meet consistently. The emergence of 5G technology offers a solution to these limitations by introducing Ultra-Reliable Low-Latency Communication (URLLC), Enhanced Mobile Broadband (eMBB), and Massive Machine-Type Communication (mMTC), each of which caters to specific IoT needs. URLLC provides near-instantaneous data transfer essential for mission-critical applications, eMBB supports high-speed data for bandwidth-intensive applications, and mMTC enables connectivity for a vast number of IoT devices. This review article examines the transformative role of 5G in enhancing IoT connectivity, discussing its applications across multiple sectors, the challenges faced in implementation—such as infrastructure demands and regulatory issues—and its promising future prospects. In doing so, the paper underscores how 5G is expected to drive IoT innovation and scalability across diverse industries, positioning it as a critical enabler of next-generation digital ecosystems.